(untitled) (Philadelphia, 2002)
This handbook is a practical, easily accessible guide to nutritional management of patients with acute and chronic renal diseases. Leading international experts present state-of-the-art information on these patients' nutritional requirements and offer dietary recommendations, with menus and lists of supplements to enhance patient compliance. Numerous tables and figures enable readers to find essential information quickly. This edition includes new chapters on the dietary approach to treating patients with kidney stones and hypertension, as well as on obesity and physical activity as they relate to patients with kidney disease.
Keywords: Kidney Diseases,Bệnh thận